Freight Forwarding Company Selection Using Hybrid IFAHP-IFTODIM Method - Pratiwi, Fara El Nandhita; Widodo, Agus; Darti, Isnani (Institute of Research and Community Outreach - Petra Christian University, 2022)
In selecting the best freight forwarding company, the concept of a Decision Support System (DSS) can be used to find the best solution from several alternatives. One of the DSS methods is the Intuitionistic Fuzzy Analytical Hierarchy Process (IFAHP) and Intuitionistic Fuzzy Tomada de Decisao Interativa Multicriterio (IFTODIM). This study applied the IFAHP method combined with the IFTODIM method to select the best freight forwarding company at PT Progressio Indonesia. PT Progression Indonesia is a manufacturing and retail company that produces furniture. There are 11 criteria used in the performance assessment of the four alternatives. This research shows that the best freight forwarding company at PT Progressio Indonesia is Kobra Express, with a comprehensive value of 1.000. The second is Herona Express, with a comprehensive value of 0.9437, followed by Indah Logistik Cargo, with a comprehensive value of 0.7005. The last is Guna Dharma Express, with a comprehensive value of 0.0000.